The Concept of Interlocking Directorship under Nigerian Corporate Jurisprudence: The Antithesis of the No Conflict Rule and Fair Competition - Iorun, Nicholas Iorember (ABUAD Private and Business Law Journal, 2018)
The separation of ownership from control in the widely-held large public companies which tap the Stock Exchange funds is one of the major developments of corporate capitalism. This separation is inherent in the formal structures of company law because the law gives distinctive roles to shareholders who are the theoretical owners of companies and to those who are the managers. There is, therefore, delegated management under a board structure and while ownership of the company vests in the financial proprietors, management is in the hands of directors. This prompts major agency problems as there are conflicts between managers and shareholders. There is potential for abuse of power by directors and to forestall this, the law has imposed the duty of care and the fiduciary duty of loyalty and good faith on directors. However, despite this legal mechanisms put in place to check directors, Nigerian law has endorsed interlocking or multiple directorship of rival companies, with damning consequences, in the absence of an elaborate anti-trust regime to regulate anti-competitive activities between companies. Using the doctrinal method, this article has analysed the concept of interlocking directorships, diagnosed the ills associated with it and brought out its effects on the directors’ duty to avoid conflict of interest and on fair competition. The article then prescribes the jettisoning of the concept from Nigeria’s companies’ statute or elaborate regulation of same, if it is to be retained, to cushion its effects.